Review and experimental illustrations of electronic load controller used in standalone Micro-Hydro generating plants - R. Raja Singh; B. Anil Kumar; D. Shruthi; Ramraj Panda; C. Thanga Raj (Engineering Science and Technology, an International Journal, 2018)
Hydraulic Governor (HG) in Standalone Micro-Hydro generating Systems (SMHS), for maintaining voltage and frequency at desired levels, is not preferred as HG is much costlier than the generator. Electronic load controller (ELC) is a cost-effective solution for this application. Resistive (dump) load at an equal rating of generator is used to maintain constant voltage and frequency at the load perturbations. However, the system receives electrical and mechanical stresses as it operates at full load throughout the life which causes degradation of its component and lifetime reduction. This paper reviews the development trends of ELC used for SMHS and identifies the shortcomings of available technology for it. After the review, it proposes a novel methodology to enhance the generator efficiency and its lifespan by reducing the amount of dump load used. Performance of generator with conventional and proposed methodologies is investigated experimentally and lifespan is estimated through temperature profile. In addition, generator protection from sensor faults is enforced in proposed controller for enhancing the reliability of the system. Keywords: Electronic load controller, Hydroelectric generator, Micro hydropower plant, Reduced dump load, Overload protection, Sensor fault detection and isolation